1992
DOI: 10.1117/12.131820
|View full text |Cite
|
Sign up to set email alerts
|

<title>Amplification without population inversion</title>

Abstract: We review three-and four-level schemes of inversionless amplification with different types of coherent pumping. We show that amplification without inversion between the "bare" states is a result of population inversion between eigenstates of the density matrix. In particular, it can be achieved due to the coherent population trapping, i.e. effective removal from the interaction with the field a fraction of atoms at lower levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 1 publication
0
15
0
Order By: Relevance
“…The atoms, initially in the lower state of the laser transition, are driven by a counterpropagating light field near or on resonance with their Doppler-shifted transition frequency, and for appropriate values of the parameters they can amplify a weak copropagating field through an exponential instability which is reminiscent of the threshold behavior of a free-electron laser [3]. This system unifies many aspects of the physics of the FEL and of the atomic laser in a mode of operation that does not require the initial preparation of a state of population inversion, a feature that is also common to the socalled inversionless lasers [4]. As in the laser, the active medium is characterized by bound states which play a key role in the amplification process, as we show in the main body of this paper, but do not possess a population inversion.…”
Section: Introductionmentioning
confidence: 95%
“…The atoms, initially in the lower state of the laser transition, are driven by a counterpropagating light field near or on resonance with their Doppler-shifted transition frequency, and for appropriate values of the parameters they can amplify a weak copropagating field through an exponential instability which is reminiscent of the threshold behavior of a free-electron laser [3]. This system unifies many aspects of the physics of the FEL and of the atomic laser in a mode of operation that does not require the initial preparation of a state of population inversion, a feature that is also common to the socalled inversionless lasers [4]. As in the laser, the active medium is characterized by bound states which play a key role in the amplification process, as we show in the main body of this paper, but do not possess a population inversion.…”
Section: Introductionmentioning
confidence: 95%
“…So, here we have another example of inversion without lasing due to atomic coherence and quantum interference, a phenomenon examined by Scully et al [6] using a microwave driven V-type system. We further continue the above analysis for the case that p#O.…”
mentioning
confidence: 89%
“…As has been shown extensively in the past decade, atomic coherence and quantum interference can lead to many interesting optical phenomena such as lasing without inversion [6], electromagnetically-induced transparency [7], enhancement of the index of refraction [8] and spontaneous emission modification [9] in multilevel systems. Using a V-type configuration which was driven by two laser fields, Meduri et al [lo] showed that an unexpected population inversion can be achieved in one of the optical transitions due to atomic coherence effects.…”
Section: Effects Of Spontaneous Emission Interference On Population Imentioning
confidence: 99%
“…There are some very nice suggestions to circumvent this problem, for example, there is the concept of lasing without inversion [9][10][11]. But up until now, any physical implementation has not survived the harsh confrontation with reality.…”
Section: Introductionmentioning
confidence: 99%